(untitled) (GEOmedia, 2015)
This paper aims to highlight the qualitative and quantitative aspects of the transformations occurring in the territory of the region of Lombardy analyzing land cover maps pertaining to different eras. To achieve this objective after building a database of geographical information on the various eras we proceeded to work by comparison with the transition matrices that allow you to highlight the steps quantity among different reporting periods. The analysis and the return of results is carried out at different geographical scales offering a complete anthropization exchanged in the territory. In particular, it highlights the diachronic analysis of land use in favor of urban nature, distinguishing inside the spread and transformation of urban-sprawl.